Constraints on oceanic meridional heat transport from combined measurements of oxygen and carbon - Resplandy, L; Keeling, R; Stephens, B; Bent, J; Jacobson, A; Rödenbeck, C; Khatiwala, S (Springer Berlin Heidelberg, 2016)
Despite its importance to the climate system, the ocean meridional heat transport is still poorly quantified. We identify a strong link between the northern hemisphere deficit in atmospheric potential oxygen (APO = O 2 + 1.1 × CO 2 ) and the asymmetry in meridional heat transport between northern and southern hemispheres. The recent aircraft observations from the HIPPO campaign reveal a northern APO deficit in the tropospheric column of − 10.4 ± 1.0 per meg, double the value at the surface and more representative of large-scale air–sea fluxes. The global northward ocean heat transport asymmetry necessary to explain the observed APO deficit is about 0.7–1.1 PW, which corresponds to the upper range of estimates from hydrographic sections and atmospheric reanalyses.